THE 5E INQUIRY LEARNING MODEL: ITS EFFECT ON THE LEARNING OF ELECTRICITY AMONG MALAYSIAN STUDENTS - Ong, Eng Tek; Govindasamy, Devi; Swaran Singh, Charanjit Kaur; Ibrahim, Md Nasir; Abdul Wahab, Norwaliza; Borhan, Mohamad Termizi; Tho, Siew Wei (Cakrawala pendidikan : CP, 2021)
The effectiveness of the 5E Inquiry Learning Model as compared to the teacher-centred traditional method on science achievement in electricity was examined in this study. The quasi-experimental pretest-posttest control group research design was utilized. A total of 65 students (33 and 32 students in the experimental and the control groups, respectively) from two Year 5 intact classes in Malaysia participated in this study. A test comprising 54 dichotomously scored items with overall KR-20 reliability of 0.84 was used in the pretest and posttest. Given the significant difference in the pretest and posttest, it was presumed that the analysis could be done using the ANCOVA. However, on further analysis, the assumption for homogeneity of the regression slope was violated and ANCOVA could not be performed. Instead, the covariate was categorized into two equally-spaced categories (i.e., low and average achievers) and further t-test supported the equivalency of the experimental and control groups. When analyzed using the t-test, the two groups differed significantly in the posttest means across the two categories of students. These findings unequivocally indicate the effectiveness of employing the 5E Inquiry Learning Model in enhancing students' science achievement among the low and average achieving students.